2010
DOI: 10.2174/1874210601004010153
|View full text |Cite
|
Sign up to set email alerts
|

Notch 1 Receptor, Delta 1 Ligand and HES 1 Transcription Factor are Expressed in the Lining Epithelium of Periapical Cysts (Preliminary Study)

Abstract: Periapical cyst is a chronic inflammatory disorder of periradicular tissues. The precise pathological mechanisms involved in periapical cyst enlargement remain unclear. Notch signaling is an evolutionarily conserved pathway with a regulatory role in cell fate decisions during development and in carcinogenesis. To date, there are no published data available on the expression of Notch signaling components in periapical cysts or any other jaw cyst. In this immunohistochemical study we have examined the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Notch-1, Notch-2, and Jagged-1 were expressed in basal and parabasal layers in most of the periapical cysts examined in the present study. As those cells behave as unipotent stem cells having the ability of cell division on inflammatory stimulation ( 12 ), it is suggested that Notch activation may be involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notch-1, Notch-2, and Jagged-1 were expressed in basal and parabasal layers in most of the periapical cysts examined in the present study. As those cells behave as unipotent stem cells having the ability of cell division on inflammatory stimulation ( 12 ), it is suggested that Notch activation may be involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Notch-1, Notch-2, and Jagged-1 were expressed in basal and parabasal layers in most of the periapical cysts examined in the present study. As those cells behave as unipotent stem cells having the ability of cell division on inflammatory stimulation (12), it is suggested that Notch activation may be involved in cell proliferation. On the contrary, in normal epidermis Notch participates in differentiation, i.e., overexpression of Notch-1 in the basal cells inhibits proliferation and promotes premature differentiation; however, overexpression in squamous cells induces hyperproliferation of basal cells and epithelial hyperplasia (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Notch signaling pathway also caused neuroinflammation and neuron damages related to inflammation in epilepsy (Wu et al, 2018). As one of the structurally similar Notch ligands, Notch‐1 has been found to interact with miRs in cancer cells (Meliou et al, 2010, Prokopi et al, 2014). Prior study revealed that in epilepsy, suppressing miR‐34a in neurons led to an increase in Notch signaling levels, accompanied by inhibited epileptiform discharges and neuron apoptosis (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%